Arab Liberal Thought after 1967
XV, 273 p.
Keywords: This volume aims at confronting the image of the Middle East as a region that is fraught with totalitarian ideologies, authoritarianism and conflict. It gives voice and space to other, more liberal and adaptive narratives and discourses that endorse the right to dissent, question the status quo, and offer alternative visions for society.